Energy auditing and efficiency of a ready–made garment factory in Bangladesh: a case study - Islam, Md. Atiqul (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2021.